Cardiopulmonary Resuscitation in Adults Over 80: Outcome and the Perception of Appropriateness by Clinicians. Issue 1 (15th December 2019) - Druwé, Patrick; Benoit, Dominique D.; Monsieurs, Koenraad G.; Gagg, James; Nakahara, Shinji; Alpert, Evan Avraham; van Schuppen, Hans; Élő, Gábor; Huybrechts, Sofie A.; Mpotos, Nicolas; Joly, Luc‐Marie; Xanthos, Theodoros; et al.
Abstract : OBJECTIVES: To determine the prevalence of clinician perception of inappropriate cardiopulmonary resuscitation (CPR) regarding the last out‐of‐hospital cardiac arrest (OHCA) encountered in an adult 80 years or older and its relationship to patient outcome. DESIGN: Subanalysis of an international multicenter cross‐sectional survey (REAPPROPRIATE). SETTING: Out‐of‐hospital CPR attempts registered in Europe, Israel, Japan, and the United States in adults 80 years or older. PARTICIPANTS: A total of 611 clinicians of whom 176 (28.8%) were doctors, 123 (20.1%) were nurses, and 312 (51.1%) were emergency medical technicians/paramedics. RESULTS AND MEASUREMENTS: The last CPR attempt among patients 80 years or older was perceived as appropriate by 320 (52.4%) of the clinicians; 178 (29.1%) were uncertain about the appropriateness, and 113 (18.5%) perceived the CPR attempt as inappropriate. The survival to hospital discharge for the "appropriate" subgroup was 8 of 265 (3.0%), 1 of 164 (.6%) in the "uncertain" subgroup, and 2 of 107 (1.9%) in the "inappropriate" subgroup ( P = .23); 503 of 564 (89.2%) CPR attempts involved non‐shockable rhythms. CPR attempts in nursing homes accounted for 124 of 590 (21.0%) of the patients and were perceived as appropriate by 44 (35.5%) of the clinicians; 45 (36.3%) were uncertain about the appropriateness; and 35 (28.2%) perceived the CPR attempt as inappropriate. The survival to hospital discharge for the nursing home patients was 0 of 107 (0%); 104 of 111 (93.7%) CPR attempts involved non‐shockable rhythms. Overall, 36 of 543 (6.6%) CPR attempts were undertaken despite a known written do not attempt resuscitation decision; 14 of 36 (38.9%) clinicians considered this appropriate, 9 of 36 (25.0%) were uncertain about its appropriateness, and 13 of 36 (36.1%) considered this inappropriate. CONCLUSION: Our findings show that despite generally poor outcomes for older patients undergoing CPR, many emergency clinicians do not consider these attempts at resuscitation to be inappropriate. A professional and societal debate is urgently needed to ensure that first we do not harm older patients by futile CPR attempts. J Am Geriatr Soc 68:39–45, 2019 Abstract : See related editorial by Monique Anderson Starks